DINAMIKA POLITIK DALAM PROSES INISIASI KEBIJAKAN TENTANG TANAH ADAT DAN HAK-HAK ADAT DI ATAS TANAH DI PROVINSI KALIMANTAN TENGAH - , Anita Tristya Wenni, Dra. Ratnawati, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study discussed the background emerged a policy on indigenous land and customary rights over land regulated through Central Kalimantan Governor Regulation No. 13 of 2009. A policy, ideally, emerged to address the issues in the society and to achieve common goals through compromise and consensus. But infrequently a policy was chosen due a purely political nature and forgetting the primary purpose as a solution to the issues faced by the society. Sometimes, a policy was emerged to satisfy the aspirations of parties to benefits authorities much and it often emerged simply as 'cradle' merely to calm the public without a clear road map for implementing the policies aiming in real to improve the community welfare. Therefore, a public policy considered as a political option of the holders of power. Based on these statements, an interesting thing to examine regarding indigenous land policies issue was the background emerging the policy by considering the factors affecting the government choice to set the contained policy and interests behind the emerging of the policy. To examine the background which emerged the policy on indigenous lands, it was used a qualitative research approach by policy analysis study, which was useful to investigate social phenomenon and human issues to generate descriptive data of written or spoken words from people and their observed behavior. By using the study type, it gained an objective picture of the actual circumstances which emerged the land policy in Central Kalimantan, which then transformed into decision-making driving factors and determination policy taken by Government of Central Kalimantan Province. The results of this study identified 4 (four) factors classified into two categories: internal and external factors. The Categorization was based on its influence on policy formation. Based on these categories, the internal factor was the existed escalation of conflict, and the external factor was the existed of organized reaction of indigenous peoples, the political commitment of the Governor and the ineffectiveness of prior legal rules.